1981
DOI: 10.1590/s0074-02761981000100006
|View full text |Cite
|
Sign up to set email alerts
|

Alguns hospedeiros reais de ectoparasitos do município de Caratinga, Minas Gerais, Brasil

Abstract: Os autores determinaram os hospedeiros reais para seis espécies de ectoparasitos na região de Caratinga, Minas Gerais, sendo quatro espécies de ácaros e duas de pulgas, utilizando-se do índice de infestação e do coeficiente de associação interespecífico hospedeiro/ parasito.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…Despite of the marked specificity found in our data, other studies have shown that laelapine mites often share different host species (e.g. Botelho & Williams 1980, Botelho et al 1981, Linardi et al 1984, Guitton et al 1986). Furman (1972) reported that laelapine mites were often associated with hosts at a higher taxonomic level (genus, family).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Despite of the marked specificity found in our data, other studies have shown that laelapine mites often share different host species (e.g. Botelho & Williams 1980, Botelho et al 1981, Linardi et al 1984, Guitton et al 1986). Furman (1972) reported that laelapine mites were often associated with hosts at a higher taxonomic level (genus, family).…”
Section: Discussioncontrasting
confidence: 66%
“…But in a few cases, ecological coefficients have been used to explain the associations and preferential hosts (Botelho et al 1981, Barros-Battesti et al 1998 or numeric analyses to cluster hosts (Lareschi 1996) and these studies have begun to clarify the level of the host-ectoparasite association (i.e. specificity/ generalization).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(c 2 = 13.62; C = 0.62 ± 0.47). According to Botelho et al (1981), these values support the recognition of the true hosts for those ectoparasites in a given study area. These results allied with the kariology constitute an important step for correct host identifications.…”
Section: Resultssupporting
confidence: 53%
“…There are several studies dealing with the Brazilian flea fauna (Guimarães 1972, Botelho et al 1981, Linardi 1985, Linardi et al 1984, 1987, Botelho & Linardi 1996, Barros-Battesti & Arzua 1997, Barros-Battesti et al 1998. However, few were done in areas of the Atlantic rain forest (Linardi 1977, Guitton et al 1986, Bicho et al 1999, Carvalho et al 2001, Bossi et al 2001).…”
mentioning
confidence: 99%